Gamification and Its Impact on Motivation and Pressure in Running Applications - Hiltunen, Vera (My University, 2025)
With the growing prevalence of exercise technology and gamified exercise applications, concerns have emerged about how gamification elements, which are designed to motivate users, may also contribute to stress and pressure if not carefully balanced. Gamification is increasingly being implemented across various settings as a powerful tool to engage and motivate individuals. For some users, the competitive aspect of gamification can shift the focus from intrinsic enjoyment to a constant desire for validation, which may ultimately decrease motivation. Therefore, it is important to redirect focus from pressure inducing elements to elements that create or enhance feelings of social inclusivity, competence, and enjoyment. The purpose of this thesis is to analyse gamification elements and study which elements cause users’ pressure in running applications. Strava serves as the central case study for this research, due to its large user base and its advanced gamification elements. This research employed mixed methods, including a survey and user interviews, to gather data on users’ experiences with gamification in Strava. In addition to this analysis, the thesis explores the development of a mock-up featuring design features aimed at reducing pressure and promoting positive user experiences. By emphasising social inclusivity, competence, and enjoyment, this research seeks to provide alternative design strategies that could alleviate the negative effects of gamification, offering insights into improving user engagement and satisfaction in running applications. The findings indicate that while some users felt pressure from competitive elements, many found them motivating or enjoyable, with a greater emphasis on personal progress.
Keywords: motivation, gamification, running applications, Strava